Care of the acutely ill adult an essential guide for nurses - Creed, Fiona; Spiers, Chrissie (Oxford : Oxford University Press, 2010)
Using a system- and case-based approach, this book equips nurses in more general wards with the knowledge and skills to care appropriately for the deteriorating patient in the clinical environment. These skills are recommended by NICE as essential for every nurse caring for acutely ill patients, and key to successful practice.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Intensive care nursing